Pengenalan Proses Pembuatan Gas Sintetik Dari Sampah Organik Kepada Siswa Sma Di Kecamatan Bangsal Kabupaten Mojokerto, Jawa Timur - Herri Trilaksana; Supadi Supadi (Scholar Center, 2022)
ABSTRACT Waste is a problem that we often encounter in society. The increase in population causes an increase in the amount of waste produced. Waste management methods that are not environmentally friendly can cause negative impacts on health and environmental damage. Unfortunately, the understanding of a clean and healthy lifestyle in society, especially among the younger generation, is still lacking. The younger generation has not been able to understand the use of simple technology that can be used to overcome this waste problem, including the concept of gasification. This community service will explain one way to deal with waste by making synthetic gas. The implementation of this community service event is divided into three sessions. The first session was a plenary presentation about the general knowledge of waste management that already exists in several big cities both domestically and abroad, up to a technical understanding of how to do it to solve the problem of waste handling in the surrounding environment. Session two is a trial session or demonstration of synthetic gas-producing equipment using a biomass reactor so that high school students can have psychomotor knowledge and abilities to operate a biomass reactor. The third session was in the form of exposure to critical input and suggestions as well as feedback so that there was a closer and communicative interaction between community service providers and the community service’s target. The results showed the high enthusiasm of the community service participants to overcome the problem of organic waste by converting it into electricity through the gasification process. Keynote: Student’sAawareness, Gasification, Waste Management. ABSTRAK Sampah adalah masalah yang sering kita jumpai di masyarakat. Pertambahan jumlah penduduk menimbulkan peningkatan jumlah sampah yang dihasilkan. Metode pengelolaan sampah yang tidak ramah lingkungan dapat menyebabkan dampak negatif bagi kesehatan dan kerusakan lingkungan. Sayangnya, pemahaman tentang pola hidup bersih dan sehat di masyarakat, khususnya di kalangan generasi muda, masih kurang. Generasi muda belum bisa memahami pemanfaatan teknologi sederhana yang dapat digunakan untuk mengatasi permasalahan sampah ini, termasuk diantaranya adalah konsep gasifikasi. Pengabdian kepada masyarakat ini akan menjelaskan salah satu cara mengatasi sampah dengan pembuatan gas sintetis. Pelaksanaan acara pengabdian kepada masyarakat ini dibagi menjadi tiga sesi. Sesi pertama merupakan pemaparan pleno tentang pengetahuan secara umum pengolahan sampah yang sudah ada di beberapa kota-kota besar baik di dalam negeri maupun di luar negeri, sampai dengan pemahaman teknis bagaimana melakukannya untuk menyelesaikan permasalahan penanganan sampah di lingkungan sekitar. Sesi dua merupakan sesi uji coba atau demonstrasi peralatan penghasil gas sintetis dengan menggunakan reaktor biomassa sehingga siswa SMA dapat memiliki pengetahuan dan kemampuan secara psikomotorik untuk melakukan pengoperasian reaktor biomassa. Sesi ketiga berupa pemaparan masukan kiritik dan saran serta umpan balik sehingga ada interaksi yang lebih dekat dan komunikatif antara penyelenggara pengmas dengan pihak sasaran atau target pengmas. Hasil menunjukkan antusiasme yang tinggi dari para peserta pengmas untuk mengatasi permasalahan sampah organik dengan mengubahnya menjadi tenaga listrik melalui proses gasifikasi. Kata kunci: Kesadaran Siswa, Gasifikasi, Pengelolaan Sampah.